ANALISIS PENGARUH FAKTOR INTERNAL TERHADAP BUDAYA MUTU PERGURUAN TINGGI SWASTA DI WILAYAH PROVINSI MALUKU - Masidonda, Jaelani La; Hariyanti, Dwi (Politeknik Negeri Ambon, 2022)
This study aims to reveal the post-covid-19 quality culture through examining internal factors that influence the internal quality culture at private tertiary institutions (PT) in the Maluku region. This research is a quantitative research, the object of research is at private universities in the Maluku region. Conducting research in February 2022-March 2023. The research sample is an internal quality auditor with a total of 43 respondents, with saturated sample criteria. The analytical tool, namely inferential analysis, is used by SPSS through multiple regression. The results of the study explain that the quality culture in post-covid 19 tertiary institutions in the Maluku region is significantly influenced by internal factors through the variables of management support, facilities and infrastructure, regulation and finance. Keywords: quality culture, management support, regulation, finance and finance